Gynura nepalensis DC. (Asteraceae) - A new angiosperm record for Bangladesh - Afroz, Sumona; Uddin, Mohammad Zashim; Hassan, Md. Abul (Bangladesh Journal of Plant Taxonomy, 2014)
Not available. DOI: http://dx.doi.org/10.3329/bjpt.v21i1.19275 Bangladesh J. Plant Taxon. 21(1): 101-104, 2014 (June)